A net-zero emissions economic recovery from COVID-19 - Allan,J; Donovan,C; Ekins,P; Gambhir,A; Hepburn,C; Reay,D; Robins,N; Shuckburgh,E; Zenghelis,D (COP26 Universities Network, 2020)
This briefing identifies key recovery policies that the UK government could introduce to both respond to the crisis of COVID-19, and support the country in meeting its commitment to reaching net-zero emissions by 2050.